Self-perception of aesthetic dental treatment: an integrative review - Priscylla Dias Fonseca FERREIRA; Vanessa Araújo CAVALCANTE; Raony Môlim de Sousa PEREIRA; Giselle Maria Ferreira Lima VERDE (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objective: This study aimed to conduct a literature review on self-perception of oral aesthetics in individuals undergoing cosmetic dental treatment and its impact on quality of life. Methods: 834 articles were found, of these, 31 articles were selected and accessed from the scientific productions indexed in the PubMed, LILACS and SciELO electronic databases. To rescue the sample, the following descriptors were used in Portuguese: estética dentária, odontologia cosmética, autoimagem and autopercepção; and in English: dental esthetics, cosmetic dentistry, self-image and self-perception, from 2016 to 2021. Results: The articles highlighted the relationship between aesthetic self-perception and the need for treatment. It was found that the aesthetic and psychosocial self-perception had a positive impact, improving the self-esteem and quality of life of individuals after undergoing aesthetic dental treatments. Conclusions: The research considered that new studies should be carried out on this theme, and that dentists should seek more knowledge related to oral and general health conditions, as well as on the self-perception of oral aesthetics, in order to prepare them for the performance. of interventions and planning of curative actions.